Maintenance olaparib rechallenge in patients with platinum-sensitive relapsed ovarian cancer previously treated with a PARP inhibitor (OReO/ENGOT-ov38): a phase IIIb trial - Pujade-Lauraine, Éric; Selle, F.; Scambia, G.; Asselain, B.; Marmé, Frederik; Lindemann, K.; Colombo, N.; Mądry, R.; Glasspool, R.; Vergote, Ignace B.; Korach, J.; Lheureux, S.; et al. (Annals of oncology, 2023)
Background - Poly(ADP-ribose) polymerase (PARP) inhibitor maintenance therapy is the standard of care for some patients with advanced ovarian cancer. We evaluated the efficacy and safety of PARP inhibitor rechallenge. - Patients and methods - This randomized, double-blind, multicenter trial (NCT03106987) enrolled patients with platinum-sensitive relapsed ovarian cancer who had received one prior PARP inhibitor therapy for ≥18 and ≥12 months in the BRCA-mutated and non-BRCA-mutated cohorts, respectively, following first-line chemotherapy or for ≥12 and ≥6 months, respectively, following a second or subsequent line of chemotherapy. Patients were in response following their last platinum-based chemotherapy regimen and were randomized 2 : 1 to maintenance olaparib tablets 300 mg twice daily or placebo. Investigator-assessed progression-free survival (PFS) was the primary endpoint. - Results - Seventy four patients in the BRCA-mutated cohort were randomized to olaparib and 38 to placebo, and 72 patients in the non-BRCA-mutated cohort were randomized to olaparib and 36 to placebo; >85% of patients in both cohorts had received ≥3 prior lines of chemotherapy. In the BRCA-mutated cohort, the median PFS was 4.3 months with olaparib versus 2.8 months with placebo [hazard ratio (HR) 0.57; 95% confidence interval (CI) 0.37-0.87; P = 0.022]; 1-year PFS rates were 19% versus 0% (Kaplan-Meier estimates). In the non-BRCA-mutated cohort, median PFS was 5.3 months for olaparib versus 2.8 months for placebo (HR 0.43; 95% CI 0.26-0.71; P = 0.0023); 1-year PFS rates were 14% versus 0% (Kaplan-Meier estimates). No new safety signals were identified with olaparib rechallenge. - Conclusions - In ovarian cancer patients previously treated with one prior PARP inhibitor and at least two lines of platinum-based chemotherapy, maintenance olaparib rechallenge provided a statistically significant, albeit modest, PFS improvement over placebo in both the BRCA-mutated and non-BRCA-mutated cohorts, with a proportion of patients in the maintenance olaparib rechallenge arm of both cohorts remaining progression free at 1 year.
Online verfügbar: 4. Oktober 2023, Artikelversion: 10. Dezember 2023
Gesehen am 02.04.2024